[Translated article] Practical Considerations About Optimal Skin Incisions/Excisions in Dermatologic Surgery with Emphasis on Incisions Orientation and Primary Cutaneous Melanoma Surgery - R. Moro; E. Nagore (Elsevier, 2022)
Dermatologic surgery has 2 main objectives: 1) to guarantee surgical radicality; and 2) to achieve optimal aesthetic and functional results. These 2 paradigms and their hierarchy must be considered when performing surgical procedures on the skin. Even the easiest intervention, the elliptical excision, presents some features that should be known to achieve such goals. One of these features is the incision orientation.The optimal incisions orientation is still matter of debate, especially because studies that compare the outcomes of performing incisions in different directions are lacking. However, some anatomical, clinical, and histological observations may point out why incising the skin in one orientation is better than another.Knowing the theory behind skin incisions/excisions become of outmost importance when dealing with primary cutaneous melanoma surgery. Especially if the melanocytic lesion is suspected to be an invasive melanoma and a sentinel lymph node biopsy will be required. Resumen: La cirugía dermatológica tiene 2 objetivos principales: 1) asegurar la radicalidad quirúrgica, y 2) obtener unos resultados estéticos y funcionales óptimos. Se tienen que considerar estos 2 paradigmas y su jerarquía cuando se realizan intervenciones quirúrgicas en la piel. Incluso la intervención más sencilla, el huso, presenta algunas características que deberían ser conocidas para obtener dichos objetivos. Una de estas características es la orientación de la incisión.La orientación óptima de las incisiones es todavía materia de debate, especialmente porque no hay estudios que comparen los resultados según la dirección de la incisión. Sin embargo, algunas observaciones anatómicas, clínicas e histológicas podrían indicar por qué cortar la piel con una orientación es mejor que otra.Conocer la teoría detrás de las incisiones/extirpaciones cutáneas se vuelve imprescindible cuando hay que enfrentarse a la cirugía del melanoma cutáneo primario. Especialmente si se sospecha que la lesión melanocítica es un melanoma invasivo y se requerirá una biopsia del ganglio centinela.